Everything Finds Itself. Issue 1 (July 2017) - Nancy, Jean-Luc
Abstract : 'Matter is the name of the impenetrable. Spirit is the name of penetration. At the extremity of a penetration there is always an impenetrable that defines the point from which there is nothing left to penetrate. Not an extraordinarily hard, thick and resistant consistency, but rather the disappearance of all consistency and therefore of all resistance. Or else more accurately the conjoined extremity of consistency and inconsistency. Of resistance and desistance. Something like the coincidence of a particle and a wave, a point and its flight, a hard nucleus and its fission. It is the point of equivalence between something and nothing. The res, the thing itself and its "that there is". The real.'